2010
DOI: 10.1097/brs.0b013e3181bfca15
|View full text |Cite
|
Sign up to set email alerts
|

Ligamentum Flavum Thickness in Normal and Stenotic Lumbar Spines

Abstract: LF thickness is an age-dependent and gender-independent phenomenon. LF is significantly thicker on the right side. The borderline between normal and pathologic LF thickness should not be set at 4 mm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
95
1
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(107 citation statements)
references
References 31 publications
10
95
1
1
Order By: Relevance
“…Thus, the dynamic change at L2-3 should be evaluated before surgery in addition to that at L3-4 and L4-5. At L5-S1, motion is stabilised by the iliolumbar ligaments and the large transverse process of the L5 vertebra, which is not the case at L3-4 and L4-5 [18]. Therefore, the rate of dynamic change at L5-S1 may be lower than that at L3-4 and L4-5.…”
Section: Discussionmentioning
confidence: 97%
“…Thus, the dynamic change at L2-3 should be evaluated before surgery in addition to that at L3-4 and L4-5. At L5-S1, motion is stabilised by the iliolumbar ligaments and the large transverse process of the L5 vertebra, which is not the case at L3-4 and L4-5 [18]. Therefore, the rate of dynamic change at L5-S1 may be lower than that at L3-4 and L4-5.…”
Section: Discussionmentioning
confidence: 97%
“…Therefore, the vertebral body anteriorly and LF posteriorly must take a major role in balancing the lower lumbar spine and handling the increased spinal load in these people (due to changes in the position of the line of gravity). The outcome is thickening of LF [78][79][80][81][82][83] and modifications of vertebral bodies, i.e., increasing vertebral body surface and decreasing vertebral height. All these alterations may lead in time to degenerative changes of the osseous and nonosseous tissues around the spinal column causing stenosis.…”
Section: Discussionmentioning
confidence: 99%
“…Also they said that thickening of LF at L4-5 has already started in subjects of 30-39years of age group. They concluded that thickening of LF was not due to the buckling of LF into the spinal canal with disc degeneration.In Abbas et al study 9 , significant changes in LF thickness were observed after the age of 40 years. It was also observed that 22 individuals of < 30 years of age (4.5% to 13.6% of these subjects) showed LF thickness of more than 4mm (depending on the vertebral level).…”
mentioning
confidence: 84%